Double Beta Decay Experiments With Loaded Liquid Scintillator - Shimizu, Itaru; Chen, Mark (Frontiers in Physics, 2019)
Liquid scintillator detectors have many properties which are highly advantageous for neutrino research at the MeV energy scale. There are various choices of additives to an organic liquid scintillator which typically function as the nuclear targets in a neutrino interaction. More recently, new techniques for loading a large amount of nuclei into liquid scintillator enable sensitive searches for double beta decay with various nuclei. KamLAND was an existing detector constructed for neutrino physics at the MeV scale, later upgraded to a sensitive detector for double beta decay (KamLAND-Zen). In this experiment, isotopically enriched xenon gas was loaded into the highly radiopure liquid scintillator. As xenon is a stable noble gas, the scintillation performance changes little, and it is safe for long-term use. To mitigate backgrounds, xenon was loaded only into the liquid scintillator in the central part of the detector, contained in a spherical nylon balloon. Owing to the large amount of xenon and low background level, the KamLAND-Zen experiment achieved the most sensitive search to date for neutrinoless double beta decay in the standard mechanism. The next phase of the experiment plans to increase the amount of xenon by almost double. In the future, sensitivity can be further enhanced by detector upgrades. SNO+ (successor to the Sudbury Neutrino Observatory) is a liquid scintillator detector that is currently being commissioned and will soon be taking data. Originally, SNO+ developed a technique to load neodymium into the liquid scintillator in order to conduct a double beta decay search with the isotope 150Nd. Later, SNO+ developed two new techniques that enable loading tellurium into liquid scintillator. The large natural abundance of 130Te and the ability to load tellurium at a significant concentration in the SNO+ liquid scintillator, while maintaining excellent scintillation optical properties, offer the prospect of a very sensitive search for neutrinoless double beta decay. This article will discuss both experiments, KamLAND-Zen and SNO+, highlighting the results achieved, the techniques involved in loading the liquid scintillator, and describing the purification of components of the loaded liquid scintillator to very low background levels.